1994
DOI: 10.1111/j.1476-5381.1994.tb13045.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tachykinin NK1 and NK2 receptors in the circular muscle of the guinea‐pig ileum and proximal colon

Abstract: 1 The aim of this study was the pharmacological characterization of tachykinin NKI and NK2 receptors mediating contraction in the circular muscle of the guinea-pig ileum and proximal colon. The action of substance P (SP), neurokinin A (NKA) and of the synthetic agonists [ Furthermore, an intraspecies heterogeneity of the NK2 receptor in the circular muscle of the guinea-pig ileum and colon is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 41 publications
6
43
0
Order By: Relevance
“…The increase in I SC to SLIGRL in the trachea was most likely due to NK 1 R-mediated stimulation of luminal Cl Ϫ secretion as it was inhibited by removal of Cl Ϫ from the bathing Krebs' solution, by inhibitors of cystic fibrosis transmembrane conductance regulator (glibenclamide) (Schultz et al, 1999) and Ca 2ϩ -activated (DIDS) (Kidd and Thorn, 2000) Cl Ϫ channels, and by three potent, selective and structurally dissimilar NK 1 R antagonists (Emonds-Alt et al, 1993;Maggi et al, 1994;Gardner et al, 1996;Moriarty et al, 2001). In addition, the increase in I SC to SLIGRL only occurred when the peptide was applied to the luminal surface of the trachea Results are expressed as increases in I SC (microamperes per square centimeter) from basal, and data points are means Ϯ S.E.M.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in I SC to SLIGRL in the trachea was most likely due to NK 1 R-mediated stimulation of luminal Cl Ϫ secretion as it was inhibited by removal of Cl Ϫ from the bathing Krebs' solution, by inhibitors of cystic fibrosis transmembrane conductance regulator (glibenclamide) (Schultz et al, 1999) and Ca 2ϩ -activated (DIDS) (Kidd and Thorn, 2000) Cl Ϫ channels, and by three potent, selective and structurally dissimilar NK 1 R antagonists (Emonds-Alt et al, 1993;Maggi et al, 1994;Gardner et al, 1996;Moriarty et al, 2001). In addition, the increase in I SC to SLIGRL only occurred when the peptide was applied to the luminal surface of the trachea Results are expressed as increases in I SC (microamperes per square centimeter) from basal, and data points are means Ϯ S.E.M.…”
Section: Discussionmentioning
confidence: 99%
“…These authors showed that the non-parallel rightward shifts of the curves and the depression of the maximal response were dependent on both the antagonist concentration and the incubation time. On the other hand, Maggi et al (1994) had shown that SR 48,968 behaved as a competitive antagonist in the guinea-pig colon. However, Patacchini et al (1994) proposed that the NK 2 receptor-selective agonist, [bAla 8 ]-NKA(4 ± 10), which was used in the experiments of Maggi et al (1994) was able to stimulate NK 1 receptors at high concentrations.…”
Section: Antagonist Effectsmentioning
confidence: 99%
“…On the other hand, Maggi et al (1994) had shown that SR 48,968 behaved as a competitive antagonist in the guinea-pig colon. However, Patacchini et al (1994) proposed that the NK 2 receptor-selective agonist, [bAla 8 ]-NKA(4 ± 10), which was used in the experiments of Maggi et al (1994) was able to stimulate NK 1 receptors at high concentrations. Thus, the nature of the antagonism of SR 48,968 appeared competitive.…”
Section: Antagonist Effectsmentioning
confidence: 99%
“…To achieve equilibrium with NK 1 receptors, each concentration of TAK-637 was added into the bath solution 30 min prior to construction of an agonist concentrationresponse curve or EFS. The effects of TAK-637 on concentrationresponse curves induced by selective tachykinin receptor agonists were investigated in the following preparations: 1) longitudinal colonic muscle showing NK 1 receptor-mediated contractions to [Sar 9 ,Met(O 2 ) 11 ]-SP or GR 73632; 2) circular colonic muscle showing NK 2 receptor-mediated contractions to GR 64349 (Maggi et al, 1994); and 3) the taenia coli muscle showing NK 3 receptor-mediated contractions to senktide (Croci et al, 1995). The blockade of nerve conduction by tetrodotoxin (TTX, 1 M) was used to distinguish between a neuronal and non-neuronal (smooth muscle) site of action of TAK-637.…”
Section: Methodsmentioning
confidence: 99%
“…The motor action of tachykinins is associated with activation of NK 1 receptors, causing contractions of intestinal muscles (Holzer and Lembeck, 1980;Maggi et al, 1994) or epithelial secretion (Perdue et al, 1987;Brown et al, 1992;Cooke et al, 1997). SP is implicated in the neurally coordinated control of motility and mucosal secretion (Greenwood et al, 1990), acting as a neurotransmitter often coreleased with acetylcholine (Bartho and Holzer, 1985;Costa et al, 1996).…”
mentioning
confidence: 99%